Peningkatan Pemahaman Konsep Pecahan Siswa Sekolah Dasar dengan Media Kertas Lipat - Yuliandari, Ria Norfika; Anggraini, Dian Mustika; Rahmah, Ulaifia Nur; Zahroo, Fathimatuz; Fatmawati, Fatmawati (Dawuh Guru: Jurnal Pendidikan MI/SD, 2024)
The background to this research is the low understanding of concepts experienced by students, and the lack of student interest in learning mathematics. For this reason, teachers must choose the right learning media so that they can increase students' understanding of concepts, as was done by the teacher in class IV MI Darul Ulum 02. This research was conducted at MI Darul Ulum 02 for the 2023/2024 academic year. This research aims to analyze the increase in understanding of mathematical concepts regarding fractions in class IV using folded paper learning media. The method used in this research is observation, directly observing the mathematics learning process and interviews with class IV teachers. The results of this research show that the use of folded paper media increases students' understanding of concepts in mathematics regarding fractions. This is shown when the teacher asks students questions, and the students can answer correctly.